2016
DOI: 10.1242/jcs.179127
|View full text |Cite
|
Sign up to set email alerts
|

An initial phase of JNK activation inhibits cell death early in the endoplasmic reticulum stress response

Abstract: Accumulation of unfolded proteins in the endoplasmic reticulum (ER) activates the unfolded protein response (UPR). In mammalian cells, UPR signals generated by several ER membrane resident proteins, including the bifunctional protein kinase endoribonuclease IRE1α, control cell survival and the decision to execute apoptosis. Processing of XBP1 mRNA by the RNase domain of IRE1α promotes survival of ER stress, while activation of the mitogen-activated protein kinase JNK by IRE1α late in the ER stress response pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
55
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 127 publications
(163 reference statements)
0
55
0
2
Order By: Relevance
“…47,48 JNK activates JUN in response to stresses such as ultraviolet irradiation or inflammation whereas ERK activates JUN in response to growth factor stimulation 53 . JNK is a well-established target of IRE1α and promotes both survival and death in response to ER stress 54 . In response to chemically induced ER stress, we have observed that JUN is phosphorylated at Ser73, which is a known substrate of JNK.…”
Section: Discussionmentioning
confidence: 99%
“…47,48 JNK activates JUN in response to stresses such as ultraviolet irradiation or inflammation whereas ERK activates JUN in response to growth factor stimulation 53 . JNK is a well-established target of IRE1α and promotes both survival and death in response to ER stress 54 . In response to chemically induced ER stress, we have observed that JUN is phosphorylated at Ser73, which is a known substrate of JNK.…”
Section: Discussionmentioning
confidence: 99%
“…The data presented here demonstrated that an ischaemic insult of 20 minutes in perfused rat hearts is sufficient to trigger the UPR. 30,33 The mechanisms involved in this pro-survival signalling response include the JNK-induced expression of anti-apoptotic genes 30 and the JNK-mediated induction of autophagic flux. Furthermore, IRE1α pathway could also be involved in elevation of both, JNK phosphorylation and cleavage of caspase-12.…”
Section: Discussionmentioning
confidence: 99%
“…The role of JNK activation in the ER stress response has also been reconsidered. [30][31][32] JNK signalling is currently accepted to have functionally distinct phases with opposing effects in the ER stress response. In contrast to the pro-apoptotic late phase, the early and transient phase of JNK activation has been reported to protect ER-stressed cells from executing apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, JNK activation has been linked to the upregulation of Manganese dependent-Super Oxide Dismutase (Mn-SOD) and catalases depending on the deacetylase SIRT1 and the FOXO transcription factor1364. In a more recent study, the early JNK response has been proposed to inhibit apoptosis67. Collectively, the results obtained in this study and other studies on various organisms suggest that the primary role of JNK signalling in thermal and solar spectrum UVR-induced oxidative stress consists of triggering a pro-survival anti-oxidant response.…”
Section: Discussionmentioning
confidence: 99%